The Relationship Between Islamic Diversity And The Economic Ethos Of Communities In The Mining Industry Area Slicy Stones Of South Kalimantan - Wahyudin; Ridhahani Fidzi; Gt. Muhammad Irhamna Husin (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
Batulicin city is known for its abundant nature. Various industries have been established with the rapid development of the area, characterized by adequate infrastructure. As social growth and changes occur, religion cannot be separated from these changes. The existing phenomenon shows that the religious life of the people in Batulicin is still strong. They enthusiastically carry out various religious rituals, and still firmly hold religious beliefs or convictions in their daily lives. The aim of this research is to explore the relationship between Islamic religion and the economic ethos of the community in the mining industry area in Batulicin. This research was designed using a qualitative approach with a phenomenological paradigm. Based on informants, it was found that there is a strong relationship between religion and economic ethos in the community in the Batulicin mining area.